Freiras ou judias? : congregação Nossa Senhora de Sion em Sergipe - Assis, Robson Dias de (2012)
In this research is listed some of the changings that occurred in Congregation Our Lady of Sion, mainly the changings that have a close relation with the behaviour that is practiced and presented by the Congregation. The aim, while the research was being done, was to perceive if the aproximation of the sisters to Judaism had modified their religious practices and, by extension, the practices of the people that interact socialy with them. It was also observed that the Congregation had a declive in the noviciate due to social transformations occurred in the 60 s and 70 s of last century. These two decades influenced not only the noviciate of the Congregation, the way to manifest yourself religiously was profoundly alterated, in other words, the religious habitus of the congregation shows that, like in other religious segments, is possible to have an official vinculation with Catholic Church and complement it with caracters from other tradition, in this case, the Judaism. At last, in the search to understand the identity of the sisters it was verified that there is a concern about to affirm themselves as catholic, however the identity shown is marked by the jewish tradition, or a hybrid identity.